Reaction to Anfal in Art (Song, Music, Theatre, Painting, Cinema) (A Critical and Analytical Study) - عومەر, مەهدی فاتیح (Sulaimani Journal for Humanities, 2025)
This study, entitled "The Impact of Anfal Operations in Kurdish Arts", aims at identifying the traces of the tragedies of the Anfal military operations in the artistic works of various genres, especially in the art of southern Kurdistan. The present paper deals, for instance, with theatrical works, and how they employ this tragic event, how dramas and movies, in addition to other art genres, use it as a theme in their structures. In order to achieve the objectives of the study, examples of the outputs of a number of artistic genres have been explored and referred to briefly and publicly in the four sections— each highlighting a specific gender (music and singing - theater - plastic art - cinema). The first section deals with Kurdish music and songs in terms of the level of impact of Anfal operations and its style in expressing this tragedy. The second topic focuses on the theater and evaluates its status after the 1991 uprising. In the third part, we discuss the impact of the Anfal in the plastic art works in terms of addressing this human disaster and what have been produced under this title. As for the last section, cinema was the main focus, as a number of the works that dealt with the Anfal were investigated. At the conclusion of this study, the researcher presented a summary of his findings, and then listed the sources of the study.